2007
DOI: 10.1159/000112322
|View full text |Cite
|
Sign up to set email alerts
|

Association between Human Paraoxonase 1 Activity and Intima-Media Thickness in Subjects under 55 Years of Age with Carotid Artery Disease

Abstract: Background: Human serum paraoxonase (PON1) protects lipoproteins against oxidation by hydrolyzing lipid peroxides in oxidized low-density lipoprotein (oxLDL); therefore, it may protect against atherosclerosis. PON1 activity and polymorphisms have been inconsistently associated with carotid artery disease. The goal of this study was to clarify the role of PON1 activity and phenotype on carotid artery disease and its correlation with some inflammatory and immune markers in subjects under 55 years with early-onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…Furthermore, in the present study, oxidized LDL levels were higher in AMD patients than in controls (Kamei et al 2007). PON1 has been shown to neutralize the harmful effects of lipid peroxides by diminishing covalent linkages between lipid peroxidation products and LDL protein, as well as the accumulating lipid peroxides in LDL (Harangi et al 2008). Baskol et al (2006) concluded that the increased ROS levels might cause increased lipid peroxidation, and thus, result in decreased antioxidant PON1 activity and increased MDA levels.…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, in the present study, oxidized LDL levels were higher in AMD patients than in controls (Kamei et al 2007). PON1 has been shown to neutralize the harmful effects of lipid peroxides by diminishing covalent linkages between lipid peroxidation products and LDL protein, as well as the accumulating lipid peroxides in LDL (Harangi et al 2008). Baskol et al (2006) concluded that the increased ROS levels might cause increased lipid peroxidation, and thus, result in decreased antioxidant PON1 activity and increased MDA levels.…”
Section: Discussionsupporting
confidence: 49%
“…It is primarily a surrogate parameter for the inherent process of atherogenesis [6], an independent predictor of stroke recurrence [7], and it represents an index of chronic stable disease. The last feature makes IMT an ideal comparison parameter to assess the connections between a possible influencing factor like serum molecules [8,9,10] or coronary disease and beginning carotid atherosclerosis [11]. On the other hand, current IMT might not reflect the acute impact of risk factor treatment on events, and progression of IMT might better predict incident disease [12].…”
Section: Introductionmentioning
confidence: 99%
“…10 However, these studies have yielded conflicting results about the relationship between PON1 polymorphisms and cardiovascular risk. 9 Harangi et al 11 reported a negative relationship between PON1 activity and carotid IMT, showing that total PON1 activity, salt-stimulated PON1 activity and arylesterase activity were negatively correlated with carotid IMT. However, 67% of the subjects in that study were with overt atherosclerosis (occlusive carotid artery disease).…”
mentioning
confidence: 99%